Robot location privacy protection based on Q-learning particle swarm optimization algorithm in mobile crowdsensing - Ma, Dandan; Kong, Dequan; Chen, Xiaowei; Zhang, Lingyu; Yuan, Mingrun (Frontiers in Neurorobotics, 2022)
In recent years, with the rapid development of science and technology, robot location-based service (RLBS) has become the main application service on mobile intelligent devices. When people use location services, it generates a large amount of location data with real location information. If a malicious third party gets these location information, it will cause the risk of location-related privacy disclosure for users. The wide application of crowdsensing service has brought about the leakage of personal privacy. However, the existing privacy protection strategies can not adapt to the crowdsensing environment. In this paper, we propose a novel location privacy protection based on Q-learning particle swarm optimization algorithm in mobile crowdsensing. By generalizing tasks, this new algorithm makes the attacker unable to distinguish the specific tasks completed by users, cuts off the association between users and tasks, and protects users' location privacy. The strategy uses Q-learning to continuously combine different confounding tasks and train a confounding task scheme that can output the lowest rejection rate. The Q-learning method is improved by particle swarm optimization algorithm, which improves the optimization ability of the method. Experimental results show that this scheme has good performance in privacy budget error, availability and cloud timeliness, and greatly improves the security of user location data. In terms of inhibition ratio, the value is close to the optimal value.